Low-fee private schools, the state, and globalization: A market analysis within the political sociology of education and development - D. Brent Edwards Jr; Taeko Okitsu; Peggy Mwanza (Arizona State University, 2019)
This study investigates the emergence and supply-demand dynamics of a market for low-fee private schools (LFPS) at the level of early childhood care and education (ECCE) in a slum of Lusaka, Zambia. Based on data collection over 1.5 years, the study reveals that, despite a government policy to support ECCE, over 90% of ECCE centers are private; that school operators tend to be former teachers, businessmen/women, and religious leaders; and that LFPSs charge, on average, 2.5 times as much as government ECCE centers for tuition, not including additional indirect costs. The paper discusses how teachers in LFPSs are caught in the middle, making less than the average income earned by others in the surrounding slum, and are unable to afford LFPS fees themselves. Importantly, the paper highlights that lower income quintiles spend a greater percentage of their income on ECCE, and that a majority of families in the study must make tradeoffs between ECCE, food, housing, and other basic expenditures in order to afford private ECCE, which is a necessity given the inadequate supply of government ECCE centers. In addition to addressing school strategies for keeping costs down, this study reports on parental decision-making when it comes to school selection. Finally, beyond a straight market analysis of LFPSs at the ECCE level in Zambia, this article also comments on how this market fits into the dialectical nature of local and global contexts. That is, it draws attention to the workings of the Zambian state and its precarious position in the global capitalist economy.